The stories clothes tell voices of working-class Japan - Horikiri, Tatsuichi 1925- (Asian voices : a subseries of Asia/Pacific/perspectives, 2016)
"This compelling social history tells the stories of ordinary people in modern Japan. Tatsuichi Horikiri spent a lifetime searching out old items of clothing and oral history accounts to shed light on those who used these items. He reveals not only the often desperate lives of these people, he illuminates their hopes, aspirations, and human values"--Provided by publisher.